2022
DOI: 10.1093/ibd/izac050
|View full text |Cite
|
Sign up to set email alerts
|

National Prevalence of Psychological Distress and Use of Mental Health Care in Inflammatory Bowel Disease

Abstract: Background Individuals with inflammatory bowel disease (IBD) have elevated symptoms of anxiety and depression. The burden of such symptoms, accompanied by functional impairment in IBD, is not well documented, nor is utilization of mental health care in this population. Methods Adults ≥18 years were identified in the cross-sectional 2015–2016 National Health Interview Survey. Responses from the Kessler Index were used to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In recent years, the prevalence of IBD has been increasing worldwide and is projected to reach 1% by 2030, creating a significant global burden 2,23 . The study showed that the proportion of mental disorders in IBD patients was 7.69%, which was significantly higher than that in non‐IBD people 24 . There is a mutual influence on the mental and physical health of IBD patients, 25 and this psychological burden not only increases the physical burden of the disease but is also related to direct and indirect costs 11–14 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In recent years, the prevalence of IBD has been increasing worldwide and is projected to reach 1% by 2030, creating a significant global burden 2,23 . The study showed that the proportion of mental disorders in IBD patients was 7.69%, which was significantly higher than that in non‐IBD people 24 . There is a mutual influence on the mental and physical health of IBD patients, 25 and this psychological burden not only increases the physical burden of the disease but is also related to direct and indirect costs 11–14 .…”
Section: Discussionmentioning
confidence: 92%
“… 2 , 23 The study showed that the proportion of mental disorders in IBD patients was 7.69%, which was significantly higher than that in non‐IBD people. 24 There is a mutual influence on the mental and physical health of IBD patients, 25 and this psychological burden not only increases the physical burden of the disease but is also related to direct and indirect costs. 11 , 12 , 13 , 14 Therefore, it is very important to identify and intervene in the psychological abnormalities of IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“… 39 It has further been shown that early intervention, before psychological distress spirals out of control, can lead to improved outcomes. 40 , 41 Due to this, it is recommended to address mental health and make referrals for support during the routine IBD visit 42 ; yet, a patient’s ability to follow through on these recommendations is limited in the United States by scarcity and out-of-pocket expense. While the Affordable Care Act (ACA) extended the insurance plans that needed to comply with the federal parity requirement for treatment of mental health conditions, 43 co-payments, and in-network requirements maintain strict conditions that present barriers for patient access.…”
Section: Barriers To Care For Patients With Ibdmentioning
confidence: 99%
“…Further, a meta-analysis of over 30,000 patients with IBD estimated the prevalence of anxiety and depression symptoms in patients with active IBD to be 57.6% and 38.9%, respectively [ 8 ]. On top of these comorbid psychiatric risks, approximately 25%-33% of patients with IBD experience symptoms of psychological distress and posttraumatic stress symptoms from medical procedures, hospital stays, disease symptoms, and pain [ 9 ]. Despite these associations, most IBD patients’ mental health concerns often remain untreated [ 1 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…On top of these comorbid psychiatric risks, approximately 25%-33% of patients with IBD experience symptoms of psychological distress and posttraumatic stress symptoms from medical procedures, hospital stays, disease symptoms, and pain [ 9 ]. Despite these associations, most IBD patients’ mental health concerns often remain untreated [ 1 , 9 ].…”
Section: Introductionmentioning
confidence: 99%